Phonon magnonics - Fung, T (2015)
This thesis reports on some recent results in the field of acoustics and magnonics. Chapter 1 reviews the literature on magnonics and GHz frequency transducers, and highlights the lack of understanding of the growth mechanism of magnetron sputtered ZnO thin films. A novel configuration for exciting magnetostatic spinwaves using ZnO transducers is proposed. Chapter 2 is an introduction to piezoelectricity and how it can be used to generate GHz acoustic waves. A detailed formulation of the Mason model is presented in chapter 3 for predicting the performance of ZnO transducers. In chapter 4, the fabrication protocol of ZnO transducers in the custom-built sputtering plant is discussed and the transducer characterisation techniques including X-ray and pulse echo measurement are described. In chapter 5, the characterised properties of the film are compared with modelling prediction. It is found that the piezoelectric and structural properties of the fabricated ZnO films are strongly correlated and are critically dependent on the sputtering conditions and thicknesses. Chapter 6 is dedicated to plasma characterisation of the sputtering conditions using Langmuir probe diagnostics. The making of the Langmuir probe system and its development are discussed. Chapter 7 examines the various possible growth mechanisms of the ZnO films with a view to understanding how the c-axis texture forms during sputtering. The results from the Langmuir probe diagnostics and X-ray characterization indicate the detrimental in uence of ion bombardment on the film qualities. It is deduced that the c-axis self texturing of ZnO films is driven dominantly by the 'survival of the fastest' mechanism. Chapter 8 describes the theoretical formulation of magnetostatic spin-wave modes and the mechanism for which the laterally propagating magnetostatic modes are coupled to local elastic standing waves. The experimental evidence (using time resolved spectroscopy) of the acoustic excitation of magnetostatic spin-waves in a YIG film waveguide is then presented in chapter 9; the excitation efficiencies at various magnetic field configurations and carrier frequencies are investigated. Finally, chapter 10 ends the thesis with the summary of results and outlooks.